Câncer do colo do útero : tendências de incidência, mortalidade e sobrevida na grande Cuiabá-MT - Souza, Paulo César Fernandes de (2017)
Cervical cancer is considered a public health problem because of its magnitude and occurrence in developing and less developed countries. Objective: To analyze the mortality rate, mortality and population survival in cervical cancer patients in Greater Cuiabá- MT. Methods: An ecological retrospective temporal and longitudinal series of five-year global survival, using information from the Mortality Information System and the PopulationBased Cancer Registry of Greater Cuiabá-MT. Incidence and mortality rates, standardized by the world standard population and gross rates were calculated from the population denominations made available by the Brazilian Institute of Geography and Statistics. Trend analysis was performed using the Joinpoint regression to estimate the Annual Percentage Change (APC) and the Average Annual Percentage Change (AAPC). The survival time was estimated from the date of diagnosis until the date of death and its probability accumulated by the Kaplan - Meier method, and to verify differences in the survival curves, the log - rank test was performed and Cox proportional hazards were calculated. Results: Cervical cancer incidence and mortality rates were higher than 20 new cases per 100,000 women and 5 deaths per 100,000 women. The trend of cervical cancer mortality, without redistribution and after redistribution, was a statistically significant reduction throughout the period (APC = -1.0% CI95% -2.0, -0.0 and -1.8; -0.2 p <0.05) respectively. The incidence of carcinoma in situ presented a tendency for stability and for cancer of the invading cervix, there was a reduction (APC = -8.4% CI95% -12.2; -4.1 p <0.05). At age, the trend remained stable in mortality, except for 60-69 years, there was a reduction (APC = -3.9% CI95% -6.9; -0.9) and in the incidence there was a reduction in the age groups from 30 to 69 years for invasive cervical cancer, and in situ there was an increase in the age group ≤ 30 years (APC = 21.1% CI95%: 2.4; 43.2). In relation to survival, 916 new cases of invasive cervical cancer were followed in the period from 01/01/2000 to 12/31/2014. Overall survival in the first year was 82.43%, in five years, 63.06%. In the Cox proportional hazards model, there was an increased risk of death for the age category ≥ 60 years (RR 1.87, 95% CI: 1.42, 2.46) and in the other neoplasms group (RR 2.14, 95%: 1.30, 3.51). Conclusion: The trend was to reduce the incidence of invasive cervical cancer and stability to carcinoma in situ. Mortality was reduced. However, observed patterns of incidence, mortality and overall survival were similar to those in the developing and least developed regions of the world, reflecting failures in access to early detection as well as timely provision of adequate treatment.